Prevalence and determinants of Contraceptive practice in Women Attending Tikrit Teaching Hospital - S. Jassim, Shatha (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Family planning assist in achieving the optimal growth and development of each member in the family and protect the women from the side effects of multiple pregnancies. The aim of this study is to determine the prevalence, awareness and practice of contraceptives, and the determinants of contraceptive use among women attending Tikrit teaching hospital.Subjects and Methods: a cross sectional hospital based study was conducted in Tikrit teaching hospital from February to May 2011. A total of 280 married women aged between 15-50years were participated in this study.Results: The prevalence of family planning practice among them was 77.1%. Despite that all of women (100%) knew about contraception but only (80%) were in favor it. Favor and practice of contraception inversely related to educational level. Among users, the modern methods were the most common methods used by women (64.3%) while only (35.7%) used the natural traditional methods. Conclusion: this study revealed high awareness about family planning methods, in the same time the prevalence of practicing it was high. Favor and practice of contraception were more pronounced in low educated and unemployed women.